Treatment of Acne Vulgaris with Tetracyline Hydrochloride: a Double-blind Trial with 51 Patients. Issue 5649 (12th April 1969) - Lane, Peter; Williamson, Donald M.
Abstract : Fifty-one patients with acne vulgaris were included in a double-blind trial to assess the therapeutic effect of 250 mg. tetracycline hydrochloride twice daily for three months. The results, assessed clinically and photographically, showed that tetracycline hydrochloride had a statistically significant beneficial effect. Hence, since it is cheap and rarely has side-effects in healthy young adults, its use is suggested, as well as local therapy, in the more severe forms of acne.